The Problem of Confrontation of the Cognitive Warfare inCase of Inter-Civilizational Conflicts among Narratives - Simonyan, Gurgen (NAS RA)
In the modern world, the revolutionary development of the new Informational technologies (IT) along with the various opportunities it has brought, also has created new challenges for humanity. The scope of these challenges is so great that it has become an insurmountable force for a separate state. Therefore, to overcome them, the states must form an alliance, and establish supranational organizations and systems, through which it will be possible to reduce and, if possible, neutralize the threats and emerging risks arising from them. One of the similar threats is “lie”: falsification, misinformation, “mass confabulation” * and fake news, the speed, volume, and diversity of which spread has turned into a “war of narratives”, in the chaos of which an urgent issue of international protection of fundamental rights and freedoms of human, also truth and justice of civilization has arisen. The subject of this article is “Narrative warfare” (NW). Purpose: is an analysis of the role of creating an “alternative past” (AP) for an “alternative future” (AF) in international relations, against a “paradigmatic future” (PF), using the substitution of meanings, symbols, and influence on the mass perception of reality, causing cognitive dissonance and mass psychosis in the affected areas. Results of the research paper show, that due to the NW, universal justice suffers, and the chain of intertwined historical perceptions of collective identity is broken. In conclusion, to defend the truth, states must unite and consolidate the world community, and establish appropriate institutions within the framework of the new world order.
Keywords: Political Studies; Political Philosophy